2016
DOI: 10.1186/s12868-016-0310-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic differences in intruder-evoked immediate early gene activation in male, but not female, vasopressin 1b receptor knockout mice

Abstract: BackgroundThe neuropeptide arginine vasopressin (Avp) modulates social behaviors via its two centrally expressed receptors, the Avp 1a receptor and the Avp 1b receptor (Avpr1b). Recent work suggests that, at least in mice, Avp signaling through Avpr1b within the CA2 region of the hippocampus is critical for normal aggressive behaviors and social recognition memory. However, this brain area is just one part of a larger neural circuit that is likely to be impacted in Avpr1b knockout (−/−) mice. To identify other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…For example, AVPR1a has a greater role in modulating anxiety in male mice 47,48 and blocking this receptor alters social play in males and females in an opposite fashion 49 . Similarly, sex related differences in AVPR1b dependent brain responses have been reported 50 . Altered AVPR expression is a consistent finding related to early-life penicillin exposure 18,41 and it is possible that sex differences in the vasopressinergic system may contribute to the sex dependent nature of the effects of this antibiotic on behaviour.…”
Section: Discussionmentioning
confidence: 75%
“…For example, AVPR1a has a greater role in modulating anxiety in male mice 47,48 and blocking this receptor alters social play in males and females in an opposite fashion 49 . Similarly, sex related differences in AVPR1b dependent brain responses have been reported 50 . Altered AVPR expression is a consistent finding related to early-life penicillin exposure 18,41 and it is possible that sex differences in the vasopressinergic system may contribute to the sex dependent nature of the effects of this antibiotic on behaviour.…”
Section: Discussionmentioning
confidence: 75%
“…The role of neuropeptides oxytocin and arginine vasopressin in regulation of social behavior, social cognition, individual stress response, depression and callous-unemotional traits has been reported to date [4,5]. In turn, impaired functioning of oxytocin and arginine-vasopressin 1b [5,6] and their receptors was demonstrated in animal models of exaggerated aggressive behavior, while a reduced oxytocin level was a predictor of aggression in humans [7]. The similarity in the amino acid sequence between oxytocin and arginine-vasopressin promotes differences in the affinity to their receptors [8], thus providing the resemblance in the processes that both neuropeptides modulate.…”
Section: Discussionmentioning
confidence: 99%
“…According to evolutionary research, specific sites in the AVPR1B gene were under positive selection related to domestication [29]a process involving the accumulation of prosocial traits. In addition, functional research indicated the relation of a reduced level of aggression in AVPR1b knockout mice [6]. Recent findings indicated the association between an impaired social behavior and altered expression of AVPR1B and OXTR genes in murine brain as a response to antibiotic treatment [30].…”
Section: Discussionmentioning
confidence: 99%
“…Two different IEGs, cFos and early growth response factor 1 (EGR1), have been studied in both Avpr1b −/− male and Avpr1b −/− lactating females following a single exposure to an intruder male. While no genotypic differences in cFos immunoreactivity were observed in either Avpr1b −/− males or Avpr1b −/− lactating females, a genotypic difference in EGR1 immunoreactivity was observed within the ventral bed nucleus of the stria terminalis (BNSTV) and the anterior hypothalamus (AHA), with male Avpr1b −/− mice having reduced EGR1 immunoreactivity in both brain regions relative to controls (Wersinger et al, 2002 ; Witchey et al, 2016 ). As both the BNSTV and AHA are implicated in the neural circuitry of aggression, we hypothesize that they may be part of the downstream circuit influenced by Avpr1b expression in the CA2 region of the hippocampus.…”
Section: The Avpr1b Is Important For Normal Aggressive Behaviormentioning
confidence: 99%
“…Further, increases in cFos expression are observed within the LS following intermale, interfemale, and maternal aggression (Kollack-Walker and Newman, 1995 ; Delville et al, 2000 ; Davis and Marler, 2003 ; Hasen and Gammie, 2005 ). It is also important to mention that the LS lies upstream of the BNSTV and AHA (Ferris et al, 1990 ; Staiger and Wouterlood, 1990 ); thus providing a potential circuit that might explain the EGR-1 data in Avpr1b −/− males (Witchey et al, 2016 ).…”
Section: The Avpr1b Is Important For Normal Aggressive Behaviormentioning
confidence: 99%